2015
DOI: 10.1111/plb.12375
|View full text |Cite
|
Sign up to set email alerts
|

Age‐associated alterations in the somatic mutation and DNA methylation levels in plants

Abstract: Somatic mutations of the nuclear and mitochondrial DNA and alterations in DNA methylation levels in mammals are well known to play important roles in ageing and various diseases, yet their specific contributions await further investigation. For plants, it has also been proposed that unrepaired DNA damage and DNA polymerase errors accumulate in plant cells and lead to increased somatic mutation rate and alterations in transcription, which eventually contribute to plant ageing. A number of studies also show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 116 publications
4
51
0
Order By: Relevance
“…Furthermore, C. revoluta is known to exhibit very slow growth (2–3 inches a year) and a relatively long life span (more than 1000 years). Perhaps, methylation-induced mutations may accumulate during extended periods of vegetative growth (Dubrovina and Kiselev 2015 ). Potentially, the meiotic correction system is failing because the reduced homology between repeats inhibits rDNA recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, C. revoluta is known to exhibit very slow growth (2–3 inches a year) and a relatively long life span (more than 1000 years). Perhaps, methylation-induced mutations may accumulate during extended periods of vegetative growth (Dubrovina and Kiselev 2015 ). Potentially, the meiotic correction system is failing because the reduced homology between repeats inhibits rDNA recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is evidence about the role of miR156 in redifferentiation during the induction of organogenesis (Liu et al, 2014) and somatic embryo induction (Wu et al, 2011). Moreover, it is well documented that prolonged cultivation of plant cells in vitro induces single nucleotide substitutions and increases the global DNA methylation level in a time-dependent fashion, which is associated with aging in plants (Dubrovina and Kiselev, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…However, this mechanism, that in natural populations acts as an adaptive tool, may cause changes that could affect the phenotype, which would endanger the maintenance of the characteristics of the conserved plants. In the conservation context, epigenetic changes take on a greater dimension if we consider that many studies relate them with genetic mutations [ 23 ]. Jiang et al [ 24 ] found higher frequency of mutations and epimutations (changes in cytosine methylation status) in Arabidopsis thaliana under salinity stress.…”
Section: Epigenetic Variation In Ex Situ Plant Conservation: the Rmentioning
confidence: 99%